SED-ML web tools: generate, modify and export standard-compliant simulation studies - Bergmann, Frank T.; Nickerson, David; Waltemath, Dagmar; Scharm, Martin (Bioinformatics, 2017)
Abstract. Summary: The Simulation Experiment Description Markup Language (SED-ML) is a standardized format for exchanging simulation studies independently of s
Gesehen am 11.05.2018